National study of NAFLD management identifies variation in delivery of care in the UK between 2019 to 2022 - Wenhao Li; David Sheridan; Stuart McPherson; William Alazawi; Kush Abeysekera; Tom Marjot; Paul Brennan; Sara Mahgoub; Tessa Cacciottolo; Theresa Hydes; Tim Hardy; Gio McGinty; et al. (JHEP Reports, 2023)
Background & Aims: Non-alcoholic fatty liver disease (NAFLD) is associated with liver and cardiovascular morbidity and mortality. Recently published NAFLD Quality Standards include 11 key performance indicators (KPIs) of good clinical care. This national study, endorsed by British Association for the Study of the Liver (BASL) and British Society of Gastroenterology (BSG), aimed to benchmark NAFLD care in UK hospitals against these KPIs. Methods: This study included all new patients with NAFLD reviewed in the outpatient clinic in the months of March 2019 and March 2022. Participating UK hospitals self-registered for the study through BASL/BSG. KPI outcomes were compared using Fisher’s exact or Chi-square tests. Results: Data from 776 patients with NAFLD attending 34 hospitals (England [25], Scotland [four], Wales [three], Northern Ireland [two]) were collected. A total of 85.3% of hospitals reported established local liver disease assessment pathways, yet only 27.9% of patients with suspected NAFLD had non-invasive fibrosis assessment documented at the point of referral to secondary care. In secondary care, 79.1% of patients had fibrosis assessment. Assessment of cardiometabolic risk factors including obesity, type 2 diabetes, hypertension, and smoking were conducted in 73.2%, 33.0%, 19.3%, and 54.9% of all patients, respectively. There was limited documentation of diet (35.7%) and exercise advice (55.1%). Excluding those on statins, only 9.1% of patients with NAFLD at increased cardiovascular risk (T2DM and/or QRISK-3 >10%) had documented discussion of statin treatment. Significant KPI improvements from 2019 to 2022 were evident in use of non-invasive fibrosis assessment before secondary care referral, statin recommendations, and diet and exercise recommendations. Conclusions: This national study identified substantial variation in NAFLD management in the UK with clear areas for improvement, particularly fibrosis risk assessment before secondary care referral and management of associated cardiometabolic risk factors. Impact and implications: This study identified significant variation in the management of NAFLD in the UK. Only 27.9% of patients with suspected NAFLD had non-invasive fibrosis assessment performed to identify those at greater risk of advanced liver disease before specialist referral. Greater emphasis is needed on the management of associated cardiometabolic risk factors in individuals with NAFLD. Hospitals with multidisciplinary NAFLD service provision had higher rates of fibrosis evaluation and assessment and management of cardiometabolic risk than hospitals without multidisciplinary services. Further work is needed to align guideline recommendations and real-world practice in NAFLD care.